THE USE OF CHAIN STORY GAMES IN SPEAKING SKILL - Awang Arningtyas; Ch. Evy Tri W. (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2019)
The objectives of the research are : to find out whether Chain Story Games can improve students’ speaking skill on narrative text and to find out how far Chain Story Games can improve students’ speaking skill at the eighth grade students especially in class VIII-A of SMP N 11 Surakarta in 2018/2019 Academic Year. The research used a Classroom Action Research (CAR) and the subject of the research was the students of eighth grade especially in class VIII-A. In implementation of the teaching and learning process, the researcher divided the research into two cycles. Cycle 1 had 2 meetings and cycle 2 had 2 meetings with post test in every cycle. Every cycle consisted of 4procedures:planning, action, observation, and reflection. For Classroom Action Research the researcher devided into two techniques, there were test consisted of oral test and non-test consisted of observation, interview, and documentation. In analyzed the data, the researcher used qualitative and quantitative data. The qualitative data consisted of data collection, data reduction, data display, and conclusion. In the quantitative data the researcher used t-test formula to conducted Pre-Test, Post-Test 1 and Post Test 2. Based on the result of this research, the mean score showed that in cycle 1 some students were still less on grammar, vocabulary, comprehension, fluency, and pronunciation. Therefore, Cycle 2 showed that the used of Chain Story Gameswas good to improve the students’ speaking skill. The findings was supported by the qualitative data of students’ responses in the field note, interview and documentation. The quantitative data improve from pre-test to post test 1 and post test 2. The students’ mean score in pretest was 48.13, post test 1 was 61.50 and post test 2 was 78.13. The result of post-test 1 by using t-test was 10.17and post-test 2 by using t-test was 9.90. Based on the research findings, it could be concluded that “The use of Chain Story Games can improve students’ speaking skill on narrative text at the eighth grade students of SMP N 1 Surakarta in 2018/2019 academic year especially in class VIII-A ”. Key word: Speaking Skill, Chain Story Games, Classroom Action Research, Narrative Text